Femtosecond laser plane-by-plane Bragg gratings for monolithic Thulium-doped fibre laser operating at 1970 nm - Theodosiou, Antreas; Aubrecht, Jan; Peterka, Pavel; Kalli, Kyriacos (My University, 2019)
The inscription of fibre Bragg gratings directly into active fibres has great potential compared with typical, nonmonolithic fibre laser configurations, offering more compact and robust lasers since the ‘weak’ sections of the laser, such as the free space components and splice joints, which are usually the main reasons for failures, are removed from the optical cavity. The last few years thulium doped fibres have attracted great interest for fibre laser applications, due to their performance and emission wavelength range, which is in the range of 1.9 to 2.1 μm. Here the laser operates in the ‘eye-safe’ region and offers advantages over the 1 μm lasers both for industrial and military applications. In this paper, we report on the inscription of a high reflectivity fibre Bragg gratings directly into different Thulium-doped silica fibres using the plane-by-plane femtosecond laser inscription method and their demonstration as monolithic fibre lasers. Fibre Bragg gratings were inscribed and characterised as fibre lasers using three fibres with different concentration of thulium ions, which influence the fluorescence properties. The monolithic structures were designed for continuous wave operation in the 1970 nm ‘eye-safe’ region and characterised in fibre laser configurations regarding the power output slope efficiency, stability and effective resonator length.
Keywords: Fibre Bragg gratings; Fibre Lasers; Monolithic; Thulium fibre